From innovation to stress: analyzing hybrid technology adoption and its role in technostress among students - Norzaidi Mohd Daud (International Journal of Educational Technology in Higher Education)
Abstract This study examines the impact of hybrid technology adoption on technostress among students, addressing critical knowledge gaps in existing research. Prior studies predominantly focus on workplace settings or analyze technostress in offline or fully online learning contexts, neglecting the complexities of hybrid education. Unlike previous research, this study positions hybrid technology as a central mediator, investigating key factors such as health and lifestyle, e-learning effectiveness, psychological and behavioral aspects, and institutional and technological support. 137 digital questionnaires were distributed to students at a public university, and hypothesis testing confirmed that all factors significantly influenced technostress through hybrid technology adoption (p < 0.05). The findings highlight hybrid technology’s dual role as both an enabler of learning and a stressor. This study contributes to a more comprehensive understanding of technostress and provides valuable insights for policymakers, universities, and industry stakeholders to develop effective strategies for optimizing hybrid learning environments.